Early impact of fixed orthodontic therapy on gingival health status in relation to weight status - Alasadi , Zaid A; Qasim, Alhan A (Journal of Baghdad College of Dentistry, 2018)
Background: fixed orthodontic appliances deleterious influence on gingival health is well documented. Association between weight status and gingival health is presented in many studies. This study aimed to evaluate how early the impact of fixed orthodontic therapy on patients` gingival health, and if there are differences of that impact among different weight status groups. Materials and Methods: Sample consisted of 54 patients (25 males, 29 females; age limits are 16 -18 years) going under the course of treatment with fixed orthodontic appliance. Patients were categorized according to their Body Mass Index (BMI) into 3 weight status groups considering WHO charts in 2007 (underweight, normal weight, overweight and obese), then determination of each patient`s gingival health status was through the criteria of the gingival index (GI) by Loe and Silness in 1963 which modified by Loe in 1967. Records of gingival index for all patients who met specific criteria were taken in three time points [before bonding (1st visit), 2 weeks after bonding (2nd visit), and 4 weeks after bonding (3rd visit)]. Also BMI of the patients were checked at each of the three visits. Results: There was a significant increase in gingival index for all BMI weight status groups after just two weeks of treatment, and the increase continues during the 3rd visit, with no significant difference in impact among weight status groups. Conclusions: oral health preventive measures should be applied rapidly and equally to all patients treated with fixed orthodontic appliances, without taking their BMI weight status in consideration.